The Influence of the Animated Film Diva The Series on Responsibility Values in Early Childhood at Kindergarten - Huda, Nurul; Yaswinda, Yaswinda; Utoyo, Setiyo; Afnida, Mutia (The Future of Education Journal, 2025)
This study aims to examine the significance of the influence of the use of the animated film media Diva The Series on the improvement of responsibility values in early childhood (EC). Responsibility is an essential character pillar; however, preliminary observations at the Angkasa Kindergarten of Padang Air Force Base indicate that the responsibility behavior of EC still needs to be enhanced. This quantitative research uses a Quasi-Experimental design (Non-Equivalent Control Group Design), involving 20 children from Group B1 and B2. The experimental group (n=10) was given the treatment of watching the animated film, while the control group (n=10) received conventional learning. Data collection was carried out using pre-test and post-test observation instruments that measured 12 responsibility behavior indicators. Descriptive analysis results showed that the average post-test score of the experimental group (32.50) was higher than the control group (29.50). The hypothesis test using Independent Samples t-Test resulted in a significance value (1-tailed) of 0.001. This value is smaller than the significance level of ???? = 0.05, indicating that there is a significant effect of the animated film Diva The Series on the responsibility values of EC. Audio-visual media proved effective as a behavioral model that aligns with children's learning characteristics.